SILVER NANOPARTICLE BASED HYDROGELS OF TULSI EXTRACTS FOR TOPICAL DRUG DELIVERY - Saha, *Anirban; Kumar Giri, Navneet; Agarwal, S.P. (International Journal of Ayurveda and Pharma Research, 2017)
The present study aimed to formulate Silver Nanoparticle based Hydrogel of Tulsi (Ocimum Sanctum) extract for Topical delivery. The Silver nanoparticles were prepared using 1mM Silver Nitrate solution and Tulsi extract. Prepared nanoparticles were characterized for particle size and zeta potential. The optimized silver nanoparticles were incorporated into three different carbopol-940 solutions 3%, 5% and 10% carbopol-940 solution to produce Gel A, Gel B and Gel C respectively for improving convenience in superficial application. In vitro and vivo drug penetration studies of nanoparticles gels were determined using dialysis membrane. The particle size was found around 14nm to 28nm. The viscosity of the nanoparticle gels were found around 7500 centiPa.S to 7900 centiPa.S respectively. The poly dispersibility value was found very low indicating uniformity of droplet size of the formulations. The drug content in gels was found in between 97.2% to 98.26%. The drug release was found to be 71.33 % to 73.6% after 6 h. The results indicated that nanoparticle based Hydrogel C is a promising vehicle for Topical delivery of Tulsi Extract.